2017
DOI: 10.1136/bmjopen-2016-013620
|View full text |Cite
|
Sign up to set email alerts
|

Disparities between research attention and burden in liver diseases: implications on uneven advances in pharmacological therapies in Europe and the USA

Abstract: ObjectivesEffective oral therapies for hepatitis B and C have recently been developed, while there are no approved pharmacological therapies for alcoholic and non-alcoholic fatty liver diseases (ALD and NAFLD). We hypothesise that fewer advances in fatty liver diseases could be related to disparities in research attention.MethodsWe developed the Attention-to-Burden Index (ABI) that compares the research activities during 2010–2014, and an estimate of disease burden of these 4 major liver diseases. The resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 47 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…It is not surprising that the burden of liver diseases as a cause of mortality is steadily increasing . We recently demonstrated that alcohol receives scant attention by the liver research community compared with other etiologies, such as viral hepatitis . Identifying the main determinants of excessive alcohol consumption at a global scale can favor preventive measures at the public health level.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that the burden of liver diseases as a cause of mortality is steadily increasing . We recently demonstrated that alcohol receives scant attention by the liver research community compared with other etiologies, such as viral hepatitis . Identifying the main determinants of excessive alcohol consumption at a global scale can favor preventive measures at the public health level.…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite this huge health and economic burden, ALD has received scarce attention compared to other types of liver disease. 11 Although the amount of alcohol intake influences its deleterious consequences, a precise threshold that is associated with increased morbidity and mortality is unclear. A recent study has shown that even low doses of alcohol intake, historically considered as protective, increase allcause mortality.…”
Section: Excessive Alcohol Consumption As a Cause Of Preventable Disamentioning
confidence: 99%
“…Despite the substantial proportion and enormous disease burden of AC, less research attention has been paid to it than to other etiologies such as viral hepatitis and nonalcoholic fatty liver disease [31]. Except for the well-known prognostic benefits of NSBB including propranolol for cirrhotic patients with portal hypertension, in patients with AC and alcoholic cardiomyopathy or congestive heart failure, NSBB improves quality of life, hemodynamics, and ejection fraction and reduces the severity of pulmonary hypertension [32,33].…”
Section: Discussionmentioning
confidence: 99%